Prevalence of Ivermectin use to prevent COVID-19 during the pandemic in Mato Grosso: cross-sectional home-based study - Nathalia Beatriz Lobo da Silva; Roseany Patrícia da Silva Rocha; Amanda Cristina de Souza Andrade; Ana Cláudia Pereira Terças-Trettel; Ana Paula Muraro (Revista Brasileira de Epidemiologia, 2023)
ABSTRACT Objective: To analyze the use of ivermectin as COVID-19 prevention method by the population of Mato Grosso in 2020. Methods: This is a home-based survey, carried out between September and October 2020, in 10 pole cities of the socioeconomic regions of State. The use of ivermectin was evaluated through the question: “Did you take ivermectin to prevent COVID-19?”. Sociodemographic variables (sex, age group, education, family income), current work situation, being benefitted by government financial programs, as well as symptoms, seroprevalence of antibodies against SARS-CoV-2, and previous diagnosis of COVID-19 were evaluated. Prevalence and their associations were estimated using the chi-square test. Results: 4.206 individuals were evaluated for prevalence of ivermectin use; 58.3% of the individuals responded positively, this rate being higher in the municipalities of the western region of the state (66.6%). There was no significant difference between sexes, but the prevalence was higher among people aged 50–59 years (69.7%), who were white (66.5%), with complete higher education or more (68.8%) and higher family income (≥3 minimum wages-64.2%). The use of this drug was even higher among participants who considered their knowledge of the disease good or very good (65.0%), who reported having symptoms of COVID-19 (75.3%), and who had been previously diagnosed with the disease (91.2%). Conclusion: There was a high prevalence of use of ivermectin as a method to prevent covid-19 by the population of Mato Grosso, indicating the need for strategies to inform the population about the risks of off-label use of drugs and to combat the advertising of drugs that are ineffective against COVID-19.